Implementasi Karakteristik Eko Arsitektur pada Fasad Rumah Susun - Christine, Shantika; Agustin, Dyan (Universitas Medan Area, 2025)
Building’s facade plays a crucial role in conveying a building's function and reflecting its identity. In apartment buildings, the facade serves as an aesthetic element to create an appealing building image, regulates light and airflow for inhabitant comfort, and provides protection against weather and environmental pollution. Indonesia's tropical climate and air pollution necessitate the adoption of Eco-Architecture in urban areas, especially in densely populated regions like loft complexes. By implementing these principles, facades can enhance environmental sustainability, improve thermal and visual comfort, and strengthen architectural expression. This study uses a qualitative descriptive analysis to explore the relation between eco architecture principles and the appearance of apartment building facades so it can enhance both environmental sustainability and aesthetic value. The research discusses the concept and implementation of apartment building designs that integrate eco-architecture principles to foster sustainable and environmentally friendly living environments. It aims to inspire architects, designers, and developers to create apartment building facades that combine sustainability with attractive aesthetic features.